Ruins of Red House, Port of Spain, Trinidad, B.W.I. - (:unkn) unknown (D. Adamson, Stationer, Port of Spain, 2010)
Exterior view showing the burnt ruins of the Red House located in Port of Spain, Trinidad. On March 23, 1903, during water riots, the Red House went up in flames. About 10 rioters died and 40 were wounded. The roof and floors of the building were destroyed.
Colour: Black and White; Style: Landscape; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Architecture--Trinidad and Tobago; Public buildings--Trinidad and Tobago; Riots--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; Historic buildings--Trinidad and Tobago; Buildings--Trinidad and Tobago; Ruins; [1903]